Potencial inseticida de plantas da família Annonaceae - Krinski, Diones; Massaroli, Angélica; Machado, Marilza (FapUNIFESP (SciELO), 2014)
The use of plants compounds for the control of insects has increased worldwide. This occurs because the vegetal insecticides contains biodegradable compounds, nontoxic products and potentially suitable for use in pest control. Plants of the family Annonaceae are standing out as biopesticides because they are bioactive naturally in addition to presenting cytotoxic activity, antitumor, vermifuge, antimicrobial, immunosuppressive, anti-emetic, inhibiting appetite, antimalarial and also insecticide. The insecticidal activity of Annonaceae is due to the presence of acetogenins, substances that act on mitochondria inhibiting the NADH -ubiquinone oxidoreductase, causing the death of insects. In this review we report the use of Annonaceae in insect control, showing that so far, only 42 species of Annonaceae have information insecticidal activity against just over 60 species of insect pests. This information shows that much research is still needed, especially to get to know the insecticidal activity of other Annonaceae species, in addition to its effects on insect pests not yet studied. So we will have as an alternative to sustainable development, new vegetal insecticides such as those obtained from different Annonaceae species, which can act as an additional tool to balance the excesses of agriculture chemical or conventional.
Insecticidal potential of the Annonaceae family plants
Keywords: Alternative control; Insecticide plants; Phyto-insecticides